Model Internalisasi Nilai-Nilai Islam dalam Pendidikan untuk Meningkatkan Karakter Religius Siswa - Kevin Gunawan; Driyan Hidayat; Sigit Kamseno; Sendi Budiargo Pratama; Ismail Mubarok; Dede Nur Zaman (International Forum of Researchers and Lecturers, 2026)
This research aims to formulate an effective model of internalization of Islamic values in improving the religious character of students in aliyah madrasas. The methodology used is descriptive qualitative with observation and document analysis techniques. The results of the study show that the main values that are internalized include aqidah, worship, and morals as a tangible manifestation of religious behavior. From these findings, this study produced the TITI Model (Transformation, Interaction, Transinternalization, and Integration) as a systematic and sustainable value internalization stage. This model has been proven to be able to significantly improve aspects of knowledge, worship practices, spiritual experiences, and social behavior of students. Internalization of values is carried out through a holistic approach that involves teacher examples, a conducive school culture, and family involvement. Thus, the TITI Model makes a theoretical contribution to the development of the concept of character education based on Islamic values, as well as a practical contribution to madrasas in designing strategies for fostering students' religiosity. This research confirms that the effective internalization of Islamic values is not only oriented to the cognitive aspect, but also emphasizes spiritual experiences and social behavior as the foundation for the formation of religious character of the younger generation.